Sustainable chemistry of chitosan assemblies prepared through templating and carbonization - Phuong, Le Thi Anh; Tuyen, Vu Phi; Ca, Nguyen Xuan; Hoa, Thi Le; Do, Phan Van; Thanh, Luong Duy; Nhan, Dang Thi Thanh; Dinh, Nguyen Thanh (Vietnam Journal of Science and Technology, 2022)
Biomimicry is a fascinating approach to inspire for preparing hierarchical structures of functional materials from nature through templating and transformation methods. In this work, abundantly discarded crab shell was used as a starting material to extract chitosan for investigating its complex self-assembly for material development. Chitosan macromolecules self-assembled in acidic media to form flexible, crack-free, transparent chitosan bioplastic-like membranes after drying. Chitosan bioplastics are further investigated for their physical properties through the chemistry of polymeric cross-linking. Under complexation, chitosan can self-assemble with tetramethylorthosilicate to form silica/chitosan composite membranes. The calcination of the silica/chitosan assemblies under air afforded freestanding mesoporous silica films. Silica materials may be used as a hard template, catalyst support, adsorbent, and in the chromatography. Alternatively, the pyrolysis of the silica/chitosan under nitrogen formed silica/carbon composites. The carbonized composite was etched the silica component away to obtain freestanding mesoporous carbon film supercapacitors. Cyclic voltammogram (CV) technique was used to evaluate electrochemical property of this sustainable chitosan-derived mesoporous carbon film. The obtained CV curves are fairly similar to a leaf-like shape from 2 mV.s-1 to 200 mV.s-1 with the specific capacitance (Cs) at 2 mV.s-1 is 210 F.g-1. Our method demonstrates that the thin-film features and hierarchical structure of the parent chitosan can be replicated in the sustainable mesoporous materials of silica and carbon.